FAKTOR RISIKO STUNTING BALITA 0-23 BULAN DI INDONESIA - Sudikno Sudikno; Sugeng Eko; Irlina Raswanti Irawan; Aditianti Aditianti; Yekti Widodo; Nuzuliyati Nurhidayati; Ade Chandra Iwansyah (Persagi, 2022)
ABSTRACT The problem of stunting in children under five is still a health problem, especially in developing countries. This study aims to determine the risk factors associated with the nutritional status of children aged 0–23 months in Indonesia. This study uses data from Basic Health Research (Riskesdas) 2018. The research design is cross-sectional. The research sample is children aged 0-23 months in Indonesia. Stunting was analyzed as the dependent variable. The independent variables were gender, age group, region (rural/urban), father's education, mother's education, father's occupation, mother's occupation, number of household members, number of children under five, access to a health center, access to the hospital, access to health practitioner, infectious diseases (diarrhea, ARI), ownership of MCH handbook, birth weight, birth length, mother's height, father's BMI, mother's BMI, father's smoking habit, mother's smoking habit, place of delivery, waste disposal, and hand washing with soap (father/mother). The number of samples analyzed was 10,779 children under two years old. The results of the analysis showed that the prevalence of stunting in children aged 0-23 months was 28.9 percent. The prevalence of stunting in babies 0-11 months was 22.4 percent lower than the prevalence of stunting in toddlers 12-23 months (36.8%). The results of multivariate logistic regression analysis showed that the risk factors associated with stunting in children aged 0-23 months in Indonesia were boys, ages 12-23. months, LBW, birth length (<48 cm), and maternal height (<145 cm). Keywords: stunting, children aged 0-23 months, risk factors ABSTRAK Masalah stunting pada anak balita masih menjadi masalah kesehatan terutama di negara berkembang. Penelitian ini bertujuan untuk mengetahui faktor risiko yang berhubungan dengan status gizi balita usia 0–23 bulan di Indonesia. Penelitian ini menggunakan data Riskesdas 2018. Desain penelitian adalah cross-sectional. Sampel penelitian adalah balita berusia 0-23 bulan di Indonesia. Variabel yang dianalisis meliputi variabel terikat, yaitu status gizi stunting. Variabel bebas meliputi: jenis kelamin, kelompok umur, wilayah (perdesaan/perkotaan), pendidikan ayah, pendidikan ibu, pekerjaan ayah, pekerjaan ibu, jumlah anggota rumah tangga, jumlah balita, akses ke puskesmas, akses ke rumah sakit, akses ke praktek tenaga kesehatan, penyakit menular (diare, ISPA), kepemilikan buku KIA, berat lahir, panjang lahir, tinggi badan ibu, IMT ayah, IMT ibu, kebiasaan merokok ayah, kebiasaan merokok ibu, tempat persalinan, tempat sampah, dan cuci tangan pakai sabun (ayah/ibu). Jumlah sampel yang dianalisis 10.779 anak umur 0-23 bulan. Hasil analisis menunjukkan prevalensi stunting pada anak usia 0-23 bulan adalah 28,9 persen. Prevalensi stunting pada bayi 0-11 bulan sebesar 22,4 persen lebih kecil dibandingkan prevalensi stunting pada anak balita umur 12-23 bulan (36,8%). Hasil analisis regresi logistik multivariat menunjukkan bahwa faktor risiko yang berhubungan dengan stunting pada anak balita umur 0-23 bulan di Indonesia adalah jenis kelamin laki-laki, umur balita 12-23 bulan, BBLR, panjang lahir (<48 cm), dan tinggi badan ibu (<145 cm). Kata kunci: stunting, balita 0-23 bulan, faktor risiko